2011
DOI: 10.1063/1.3592737
|View full text |Cite
|
Sign up to set email alerts
|

Significant ferrimagnetism observed in Aurivillius Bi4Ti3O12 doped by antiferromagnetic LaFeO3

Abstract: Highly crystalline quality c-axis epitaxial nLaFeO3–Bi4Ti3O12 (n=0.5,1.0,1.5) thin films were deposited on SrTiO3 (001) substrates by pulsed laser deposition. The x-ray diffraction and transmission electron microscopy characterizations confirm that there are designed even-odd number perovskite-block structures in n=0.5 and 1.5 films while it has even-even number ones in n=1.0 films. The remarkable physical property of n=0.5 and 1.5 samples is the presence of ferrimagnetism even up to room temperature. While it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…confirmed that Co can replace Ti in a BiT/LCO superlattice film, using both the experimental result and density functional theory (DFT) electronic calculation3. Fe could also substitute for Ti in the perovskite blocks randomly, as was verified in the case of the fabrication of a Bi 4 Ti 3 O 12 film doped with LaFeO 3 1415. Consistent with these previously reported results, Co and Fe ions appear to replace Ti ions at the perovskite blocks of BLT in our experiment, as we confirmed that the BLCT and BLFCT bandgaps are narrower than that of the BLT film.…”
Section: Resultsmentioning
confidence: 55%
“…confirmed that Co can replace Ti in a BiT/LCO superlattice film, using both the experimental result and density functional theory (DFT) electronic calculation3. Fe could also substitute for Ti in the perovskite blocks randomly, as was verified in the case of the fabrication of a Bi 4 Ti 3 O 12 film doped with LaFeO 3 1415. Consistent with these previously reported results, Co and Fe ions appear to replace Ti ions at the perovskite blocks of BLT in our experiment, as we confirmed that the BLCT and BLFCT bandgaps are narrower than that of the BLT film.…”
Section: Resultsmentioning
confidence: 55%
“…Meanwhile, enhanced ferromagnetism could be observed by half substitution of Fe 3 þ by Co 3 þ in BTF because of the ferromagnetic interaction between the adjacent Fe 3 þ and Co 3 þ ions [24][25][26]. Recently, Wu et al [27] reported that Bi 4 LaTi 3 FeO 15 (BLTF) films, which could be viewed as an atomic stacking of three-layered ferroelectric compound BIT and perovskite antiferromagnetic material LaFeO 3 , show more obvious room temperature ferromagnetism than that of BTF based materials. However, the investigations of ferroelectric and dielectric properties for BLTF material have not been reported until now.…”
Section: Introductionmentioning
confidence: 96%
“…As mentioned, Bi 4 Ti 3 O 12 has well-established high temperature ferroelectric properties [22,23], that can be enhanced by the substitution of Bi by Nd causing enlarged remnant polarization [24][25][26] accompanied by other changes of structural and physical properties [27][28][29][30][31]. Recently, there have been several investigations on the effects of doping Bi 4 Ti 3 O 12 by various magnetic species [32][33][34][35][36][37][38]. However, these materials do not acquire magnetic long range order even at low temperatures.…”
Section: Introductionmentioning
confidence: 99%